A study of the impact of internet use on the mental health of rural older adults—empirical analysis based on China General Social Survey 2021 data - Hu, Jiangwei; Zhang, Guocai; Wang, Mingda (Frontiers in Public Health, 2024)
BackgroundIn the context of the era of both digitalization and aging, Internet use plays an important role in supporting the rural older adults to actively integrate into the digital society and improve their mental health.PurposeTo explore the impact of Internet use on the mental health of rural older adults and the mediating role of their social participation.MethodsBased on the latest data from the China General Social Survey (CGSS) 2021, the study utilized linear regression analysis to explore the impact of Internet use on the mental health of rural older adults and the mediating role of their social participation.ResultsThe two important results of the analysis are: (1) internet use is significantly and positively related to the mental health of rural older adults, and (2) internet use can have an indirect effect on the mental health of rural older adults through two pathways: (a) the complete mediating effect of social participation;(b) partial mediating role of friend-gathering type participation.DiscussionInternet use, social participation, and friend-gathering type participation all have an effect on the mental health of rural older adults. The research results reveal the impact of Internet use on the mental health of rural older adults and its mechanism, which is helpful to provide useful enlightenment for improving the mental health of rural older adults in the Internet era.